Simulation-level performance analysis of a Li-Fi communications system for high-speed data transmission (2020)
The high wireless requirements in access, capacity and security demanded by today's society together with the great congestion of the radio spectrum has led to looking for new technological solutions such as Light Fidelity (Li-Fi). This paper shows the design and implementation of a Li-Fi communications system within an indoor environment used the optical OFDM modulation technique with asymmetric clipping (ACO-OFDM) through MATLAB software. System performance is analyzed in terms of bit error rate (BER) and bit to noise power ratio (Eb/No) taking into account receiver position, QAM modulation order and transmission rate. The results show that the performance of the system depends directly on the position of the receiver, in addition to high transmission rates the multipath degrades the performance of the system.